Report on Consolidation of Holdings in Madhya Pradesh (Pilot Survey, 1956-57) - Research Programmes Committee, Planning Commission (Research Programmes Committee, Planning Commission, Government of India, 1962)
The Report on Consolidation of Holdings in Madhya Pradesh (Pilot Survey, 1956-57) by N. M. Joglekar provides a detailed examination of the impact of land consolidation on agricultural holdings in the Chhattisgarh region. Initiated to reduce fragmentation and improve productivity, the consolidation movement significantly decreased the number of survey numbers by approximately 80%, while increasing the average size of holdings by 489%, thereby enhancing farm management efficiency and facilitating contiguous land cultivation. The study highlights improvements in irrigation practices, crop diversification, and gross-cropped areas, particularly in villages such as Chandkhuri, Bendri, and Amora, while noting that consolidation led to increased land values and better utilization of resources. However, persistent challenges remain, as inheritance, land transfers, and socio-economic pressures continue to cause sub-division and scattered holdings, particularly among larger landholders. Comparative analysis between consolidated and non-consolidated villages indicates that consolidation initially reduced scatteredness and improved productivity, but long-term trends reveal gradual re-fragmentation, emphasizing the need for continuous monitoring and supportive policies. The report recommends legislative measures to curb fragmentation due to inheritance, promotion of cooperative farming, and integration of consolidation with agricultural innovations such as soil conservation and water management to ensure sustainable productivity. Overall, the findings underscore that while land consolidation has significantly transformed agricultural practices and land management in Chhattisgarh, effective strategies are essential to address emerging challenges of sub-division, scattered holdings, and long-term farm sustainability, making it a critical consideration for policymakers in rural development and agricultural reform.
Research Programmes Committee, Planning Commission
Keywords: Land Consolidation; Agricultural Holdings; Chhattisgarh; Fragmentation; Sub-Division; Irrigation Practices; Crop Patterns; Land Values; Scattered Holdings; Inheritance; Farm Productivity; Rural Development